Antidotes for aluminum phosphide poisoning – An update. (2018) - Karimani, Asieh; Mohammadpour, Amir Hooshang; Zirak, Mohammad Reza; Rezaee, Ramin; Megarbane, Bruno; Tsatsakis, Aristidis; Karimi, Gholamreza
Abstract: Aluminum phosphide (AlP), an inexpensive solid fumigant, is frequently used for grain conservation despite its alleged high toxicity. Increased utilization of AlP for agricultural and non-agricultural purposes during the last four decades has resulted in increment of AlP-attributed poisoning numbers. Moreover, due to its limitless accessibility in developing countries, AlP has been increasingly used for suicide. Moisture-exposed AlP undergoes a chemical reaction producing phosphine gas, which in turn inhibits cytochrome oxidase and impedes cellular oxygen consumption. Lethality remains elevated reaching rates of >50% and no effective antidote is available. Nevertheless, experimental and clinical studies suggested that magnesium sulfate, melatonin, N -acetylcysteine, glutathione, sodium selenite, vitamin C and E, triiodothyronine, liothyronine, vasopressin, milrinone, Laurus nobilis L., 6-aminonicotinamide, boric acid, acetyl-L-carnitine and coconut oil, may serve as antidotes by reducing the deleterious oxidative properties of AlP. This article reviews the afore-mentioned chemicals suggested to specifically treat AlP poisoning and discusses their protective mechanisms and main outcomes.